INTEGRATING THE IMPACT OF COUNTRY OF ORIGIN (COC) AND CONSUMER ETHNOCENTRISM (CE) ON GLOBAL MARKETING (GM) AND GROWING CONSUMER TRENDS (GCT) EVIDENCES FROM PHARMACEUTICAL INDUSTRIES IN INDONES - Batu, Kardison Lumban (Journal of Management and Business Review, 2014)
The current research is empirically investigated the impact of country of origin and consumer ethnocentrism on growing customer trend directly also through global marketing as mediating variable. It is also assessed the impact of global marketing on growing consumer trend. By deploying Structural Equation Modeling with AMOS, three independent variables were analyzed, country of origin (CoC), global marketing (GM), consumer ethnocentrism (CE) and growing consumer trend (GCT) as dependent variable. The findings showed that both country of origin (CoC) and consumer ethnocentrism (CE) have significant effect on global marketing (GM) as well as on growing consumer trend (GCT). Further, global marketing (GM) successfully mediated and showed significant effect of both country of origin and consumer ethnocentrism. Finally global marketing has significant impact on growing consume trend.